12 October, 04:51
If a sequence is defined recursively by f (o) = 3 and f (n+1) = - f (n) + 5 for n≥0, then f (2) is?
12 October, 05:14
f (0) = 3 and f (n+1) = - f (n) + 5 for n≥0
so f (1) = - f (0) + 5 = - 3 + 5 = 2
f (2) = - f (1) + 5 = - 2 + 5 = 3
Know the Answer?
New Questions in Mathematics
Which of the following is NOT a property of the chi-square distribution? A. The mean of the chi-square distribution is 0. B. The chi-square distribution is not symmetric. C.
What are the two land biomes with the warmest temperatures?
Write the expression in factored form: 16m4 power - n4 power
Facts about freshwater
Fred is conducting research for Burger King to find out if the Chesapeake community prefers their burgers or McDonalds.
Which ordered pair represents the y-intercept of the graph of the equation y=-4x-7
Which issue has caused an ongoing conflict between isreal and its neighboring nations
After Mao's death what reforms did China's government make and what reforms did they block?
Identify the type of sentence. The officer ran into the house where the fugitive was hidden. simple sentence compound sentence complex sentence compound-complex
True or false all fungi have chitin in their cell walls
» If a sequence is defined recursively by f (o) = 3 and f (n+1) = - f (n) + 5 for n≥0, then f (2) is?